Characterization of anadromous Arctic char winter habitat and egg incubation areas in collaboration with Inuit fishers - Dubos, Véronique; St-Hilaire, André; Laurion, Isabelle; Bergeron, Normand E. (Arctic science, 2024)
In Nunavik, anadromous Arctic char spend more than 6 months under ice-covered habitats, mainly in lakes. Their winter habitats in this region have been scarcely studied due to the challenging logistics in the Arctic. In this study, we worked with Inuit fishers to characterize the winter habitat and incubation areas used by Arctic chars in five overwintering lakes and one lentic river reach. The collaborating fishers determined char occupancy of certain areas related to fishing sites (presence, absence, and spawning) and conducted measurements to characterize the sites while performing their fishing activities. The data showed that incubation areas were associated with significantly shallower depths and warmer (albeit not statistically significant) lake bottom temperatures than sites where no spawning occurs, which is beneficial for egg maturation. The productivity of these areas is also beneficial for fry that hatch during winter. Adult and post-smolt habitats tended to be associated with cold littoral zone, but their habitat did not show any other distinct characteristics. This exploratory study adds insights into the cryptic characteristics of the Arctic char winter habitat use, thanks to the Inuit fishers’ knowledge of fish habitats and movements, and the experience and expertise they have acquired working in the local environment.